ChatBlock: A Block-Based Chatbot Framework for Supporting Young Learners and the Classroom Authoring for Teachers - Chutiporn Anutariya; Hathaichanok Chawmungkrung; Watanee Jearanaiwongkul; Teeradaj Racharak (Technologies)
Chatbots have been used as a digital interactive learning tool in education. Designing a chatbot for young students has challenges in their capability to formulate sentences by typing. Teachers have a challenge to develop a chatbot for desired purposes as well as to suit their classes. This research proposes a ChatBlock framework that provides ChatBlock Tutor and ChatBlock Classroom interfaces to serve the target users. ChatBlock Tutor is designed as a block-based interface to support young students to connect various types of blocks for creating sentences. The formulated block-based sentences are used to make a conversation with the chatbot. On the other hand, the ChatBlock Classroom is developed to support teachers in preparing customizable content for a classroom in various formats, i.e., Q&As, learning materials, exercises, and quizzes. Finally, the design and development of ChatBlock is discussed and two case studies in primary schools are elaborated. We conduct a preliminary evaluation with a selected primary school and report the lessons learned from our study.